2008
DOI: 10.1007/s11926-008-0038-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-crystalline and crystalline rheumatic disorders in chronic kidney disease

Abstract: Rheumatic syndromes are cause for morbidity in patients with end-stage renal disease. Recent advances in understanding the role of tissue remodeling have provided insight into the pathogenic mechanisms responsible for some of these manifestations. Here, we survey recent and clinically relevant advances in translational research that impact our understanding of rheumatic syndromes seen in patients with significant renal disease. The management of acute and chronic crystalline arthropathies in chronic kidney dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 97 publications
0
18
0
Order By: Relevance
“…Further, self-report could overinflate the prevalence of gout in the US as several studies show low validation rates with self-reported gout [53,54]. It should be noted that pseudogout is also associated with CKD [55] and in the absence of confirmatory arthrocentesis could be misclassified as gout. However, in sensitivity analyses using a more specific definition of gout, we observed the same relationship between CKD stages and gout.…”
Section: Discussionmentioning
confidence: 99%
“…Further, self-report could overinflate the prevalence of gout in the US as several studies show low validation rates with self-reported gout [53,54]. It should be noted that pseudogout is also associated with CKD [55] and in the absence of confirmatory arthrocentesis could be misclassified as gout. However, in sensitivity analyses using a more specific definition of gout, we observed the same relationship between CKD stages and gout.…”
Section: Discussionmentioning
confidence: 99%
“…Oxalate arthritis may result from deposition of calcium oxalate crystals within bones, tendons, cartilage, and synovium. From these sites the crystals are thought to gain entry into the synovial fluid where they invoke an inflammatory response 44 causing joint effusions and arthralgias 45, 46 . Alternatively, supersaturation of calcium oxalate within the synovial fluid itself may lead to local crystal formation, especially when fluid is removed during dialysis, a phenomenon referred to as articular hyperconcentration 47 .…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…Typical joint involvement includes the proximal interphalangeal and metacarpophalangeal joints, knees, elbows and ankles 48 . X-rays of the joints in hyperoxaluria may reveal calcification around the joints and within tendon sheaths and soft tissue 45 . Chondrocalcinosis of the metacarpophalangeal and metatarsophalangeal joints may be seen 48 .…”
Section: Signs and Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to HH the prevalence of hyperparathyroidism in patients with CC is low 10. The association between hypomagnesia and CC has been mainly demonstrated in patients with Gitelman’s or Bartter syndrome 10 11. Given the low incidence of sporadic CC in patients under the age of 55, current opinion is that it is reasonable to screen such patients with CC for the above metabolic conditions.…”
Section: Discussionmentioning
confidence: 92%